Fixation and Mounting of Porcine Aortic Valves for use in Mock Circuits. Issue 10 (October 2013) - Schlöglhofer, Thomas; Aigner, Philipp; Stoiber, Martin; Schima, Heinrich
Purpose: Investigations of the circulatory system in vitro use mock circuits that require valves to mimic the cardiac situation. Whereas mechanical valves increase water hammer effects due to inherent stiffness and do not allow the use of pressure lines or catheters, bioprosthetic valves are expensive and of limited durability in test fluids. Therefore, we developed a cheap, fast, alternative method to mount valves obtained from the slaughterhouse in mock circuits. Methods: Porcine aortic roots were obtained from the abattoir and used either in native condition or after fixation. Fixation was performed at a constant retrograde pressure to ensure closed valve position. Fixation time was 4 h in a 0.5%-glutaraldehyde phosphate buffer. The fixed valves were molded into a modular mock circulation connector using a fast curing silicone. Valve functionality was evaluated in a pulsatile setting (cardiac output = 4.7 l/min, heart rate = 80 beats/min) and compared before and after fixation. Leaflet motion was recorded with a high-speed camera and valve insufficiency was quantified by leakage flow under steady pressure application (80 mmHg). Results: Under physiological conditions the aortic valves showed almost equal leaflet motion in native and fixed conditions. However, the leaflets of the native valves showed lower stiffness and more fluttering during systole than the fixed specimens. Under retrograde pressure, fresh and fixed valves showed small leakage flows of <30 ml/min. Conclusions: The new mounting and fixation procedure is a fast method to fabricate low cost biologic valves for the use in mock circuits.